Catalytic hydrogenation: novel process for valorization of 3-hydroxybutyric acid and advanced in situ infrared spectroscopy applied to CO2 conversion - Barros, João Lucas Marques (Universidade Federal de São Carlos, 2026)
A novel aqueous-phase hydrogenation reaction was developed for the conversion of 3-hydroxybutyric acid (HBA) to 1,3-butanediol (1,3-BDO) over catalysts composed of Ru supported on TiO2, SiO2, and C. Analyses using XRD and Raman spectroscopy indicated strong metal-oxide interaction in the Ru/TiO2 samples, while weak interaction of Ru with SiO2 led to crystallization of the Ru species. Preliminary catalytic tests with a commercial Ru/C catalyst showed that higher H2 pressure and low temperature (130 ºC) enabled selective hydrogenation of HBA to 1,3-BDO. Compared to the commercial catalyst, the synthesized Ru/TiO2 and Ru/SiO2 catalysts were more selective towards 1,3-BDO, achieving 38% selectivity with a catalyst composed of 2.0% Ru supported on TiO2. The SiO2-supported catalyst was significantly more active (62% HBA conversion at 150 ºC) than the TiO2-supported counterpart, but was also more prone to side reactions leading to 2-propanol and 2-butanol. Stability experiments with the 1,3-BDO product revealed that the Ru-based catalysts promoted side reactions originating from 1,3-BDO, especially over the SiO2-supported catalyst, which could explain the lower selectivity observed in the catalytic HBA hydrogenation. A mechanistic investigation indicated that 1,3-BDO could undergo dehydration to 2-butanol and dehydrogenation to 4-hydroxy-2-butanone, a possible intermediate in the formation of 2-propanol by a C-C cleavage pathway.
Hidrogenação catalítica: novo processo para valorização do ácido 3-hidróxibutírico e espectroscopia no infravermelho in situ avançada aplicada à conversão de CO2
Keywords: Valorização do ácido 3-hidróxibutírico; Produção de 1,3-butanodiol; Hidrogenação; Catalisadores de Ru; 3-hydroxybutyric acid valorization; 1,3-butanediol production; Hydrogenation; Ru catalysts; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA; 9. Indústria, Inovação e Infraestrutura